Emerging role for interferons in respiratory viral infections and childhood asthma - Bosco, Anthony (Frontiers in Immunology, 2023)
Respiratory syncytial virus (RSV) and Rhinovirus (RV) infections are major triggers of severe lower respiratory illnesses (sLRI) in infants and children and are strongly associated with the subsequent development of asthma. Decades of research has focused on the role of type I interferons in antiviral immunity and ensuing airway diseases, however, recent findings have highlighted several novel aspects of the interferon response that merit further investigation. In this perspective, we discuss emerging roles of type I interferons in the pathogenesis of sLRI in children. We propose that variations in interferon response patterns exist as discrete endotypes, which operate locally in the airways and systemically through a lung-blood-bone marrow axis. We discuss new insights into the role of interferons in immune training, bacterial lysate immunotherapy, and allergen-specific immunotherapy. Interferons play complex and diverse roles in the pathogenesis of sLRI and later asthma, providing new directions for mechanistic studies and drug development.